KUALITAS PELAYANAN BERBASIS ELECTRONIC GOVERNMENT PADA APLIKASI LPD PECATU MOBILE DI DESA ADAT PECATU KABUPATEN BADUNG - Arneta Putri, Ni Luh Indah; Purnamaningsih, Putu Eka; Prabawati, Ni Putu Anik (CITIZEN CHARTER, 2024)
LPD Pecatu Mobile application is an online service innovation that has been implemented since 2019. The application is implemented in order to make customers are able to access information and make transactions by utilizing technology and information. The purpose of implementing the LPD Pecatu Mobile is to provide convenience and bring the LPD of Pecatu Village closer to its customers. There are many service features that customers can use in the application. Applications can be downloaded in the AppStore for iPhone users and in the PlayStore for Android users. The existence of this application will facilitate the work of LPD Pecatu Village employees and customers no longer need to come to the office to receive services. This study aims to find out how the quality of service based on electronic government is on the LPD Pecatu Mobile application in the Pecatu Village, Badung Regency. In this study the author uses a type of qualitative research with descriptive methods. The analysis of this study uses the theory of E-GovQual from Papadomichelaki and Mentzas . The results of the study show that the implementation of the Pecatu Mobile LPD application has been going well but not fully optimal. This is because there are still several problems in the dimensions including socialization that has not run optimally, sometimes there are errors in the application, the application users are still less and are fully active using the application, the iOS users have not been able to transfer between savings accounts. Recommendations that can be given are forming a socialization team on a regular basis so that the socialization schedule is properly scheduled, optimizing door to door socialization and social media, creating an official Instagram account for LPD Desa Adat Pecatu, adding contact persons to the application. Keywords: Public Service, Electronic government, LPD Pecatu Mobile Application